FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ANEMIA PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS AIR ITAM KOTA PANGKALPINANG: Ardestiani, Fitri Rizkiah, Misyati S Asmaruddin (Biro Riset, Inovasi dan Pengabdian kepada Masyarakat, Universitas Anak Bangsa, 2021)
gr%. Anemia of pregnancy is called “potential danger to mother and child” (potential harm to mother and child). The data from Public Health center Air Itam show that from total 440 mothers checking their pregnancy in 2017 and 2 mothers (0.4%) were having anemia, from total 447 mothers checking their pregnancy in 2018 and 11 mothers (2.4%) were having anemia, and from total 469 pregnant mothers checking their pregnancy in 2019 and 108 (23%) were having anemia. The purpose of this study to know the related factors with the cases of anemia on pregnant mothers in the work area of Public Health center Air Itam in year 2020. The research employs a cross-sectional research design. The population of this research is all pregnant mothers visiting Public Health center Air Itam in year 2019 with total number of 469 pregnant mothers. The sample of this research is 90 pregnant mothers. The data are collected by interviewing using questionnaire and observation, the data are then analyzed by univariate and bivariate using chi square test.The result of data analysis shows the related factors forward the occumence of anemia on pregnant mothers are mother age (p=0,001; POR=5,200), parity (p=0,000; POR=5,659), mother knowledge (p=0,002; POR=4,353), pregnancy range (p=0,002; POR=4,420), family income (p=0,000; POR=7,125), Fe tablet consuming pursuance (p=0,000; POR=7,800), frequency of antenatal care (p=0,000; POR=9,462), mothers education (p=0,000; POR=6,760). Whereas, the most dominant factors is the frequency of antenatal care (p=0,000; POR=9,462).